Superior catalytic effects of FeCo nanosheets on MgH2 for hydrogen storage. Issue 33 (6th August 2019) - Yang, Xinglin; Ji, Liang; Yan, Nianhua; Sun, Ze; Lu, Xiong; Zhang, Liuting; Zhu, Xinqiao; Chen, Lixin
Abstract : FeCo nanosheets covered the surface of MgH2 and accelerated the dissociation and recombination of H2 molecules. Abstract : Magnesium hydride (MgH2 ) is considered as a promising hydrogen storage material for "hydrogen economy" due to its high capacity; however, its stable thermodynamics and slow kinetics hinder its practical applications. Transition metal catalysts attract intense interest in modifying MgH2 systems. Herein, FeCo nanosheets with a thickness of 50 nm were successfully prepared and confirmed to have superior catalytic effects on MgH2 . The nano-FeCo-catalyzed MgH2 started to release hydrogen at 200 °C which ended at 320 °C, while the hydrogen desorption process of pure MgH2 occurred at 350–420 °C. Besides, the dehydrogenated FeCo-containing sample could rapidly take up 6.7 wt% H2 within 1 min at 300 °C. Furthermore, after doping with nano-FeCo, the activation energy of hydrogen desorption and absorption was dramatically reduced to 65.3 ± 4.7 kJ mol −1 and 53.4 ± 1.0 kJ mol −1, respectively. In a word, our findings may provide references for designing and producing nano-level intermetallic catalysts for the research area of hydrogen storage or other energy-related research.